2020
DOI: 10.1186/s12911-020-1101-8
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approaches to predict peak demand days of cardiovascular admissions considering environmental exposure

Abstract: Background: Accumulating evidence has linked environmental exposure, such as ambient air pollution and meteorological factors, to the development and severity of cardiovascular diseases (CVDs), resulting in increased healthcare demand. Effective prediction of demand for healthcare services, particularly those associated with peak events of CVDs, can be useful in optimizing the allocation of medical resources. However, few studies have attempted to adopt machine learning approaches with excellent predictive abi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 45 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…25 Therefore, we separated the hysteresis effects of air pollutants and meteorological conditions on cardiovascular mortality in Guangzhou using an over-dispersed GAM and chose the lag day based on minimum generalized cross validation (GCV) values, which measure the model's fit. 26 Effects of single day lags (from lag0 to lag6) and cumulative day lags (from lag01 to lag06) were taken into consideration. 27…”
Section: Methodsmentioning
confidence: 99%
“…25 Therefore, we separated the hysteresis effects of air pollutants and meteorological conditions on cardiovascular mortality in Guangzhou using an over-dispersed GAM and chose the lag day based on minimum generalized cross validation (GCV) values, which measure the model's fit. 26 Effects of single day lags (from lag0 to lag6) and cumulative day lags (from lag01 to lag06) were taken into consideration. 27…”
Section: Methodsmentioning
confidence: 99%
“…For SVM model, a radial basis function (RBF) ke, rnel is used, together with regularization parameter C of 1.0. ANN, inspired by biological neural networks, has a remarkable self-learning ability to investigate the meaning and rules of complicated data [ 30 , 31 ]. For ANN model, a three-layer feedback architecture (i.e., one input layer, one hidden layer with 100 neurons, and one output layer) was performed ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that mother's occupational exposure to chemicals was a risk factor for hypospadias, and it suggested that the use of hairdressing cosmetics in early pregnancy might affect the incidence of hypospadias in newborns. Cardiovascular disease is the leading cause of patient death worldwide, a large number of studies have shown that environmental factors ( 11 ) such as air pollution and temperature changes lead to an increased risk of cardiovascular disease incidence. Tian et al ( 12 ) have used the Poisson regression model to link the increase of temperature with the increase of the number of hospitalized patients with cardiovascular diseases and their subtypes.…”
Section: Introductionmentioning
confidence: 99%